The matter of wonder Abhinavagupta's panentheism and the new materialism - Biernacki, Loriliai (New York Oxford University Press, 2023)
"The current discourse of New Materialism seeks to chart a way of addressing our contemporary predicament around environmental destruction through reassessing our relationship and attitudes to matter. This book argues that the panentheism of the 11th century Indian Hindu thinker Abhinavagupta offers a cogent philosophical model that gives us new ways of thinking about matter, which can help a contemporary New Materialist thought. What makes panentheism an attractive model for Abhinavagupta's philosophy is its Tantric impetus towards both the materiality of the world and the transcendence of divinity, proposing a philosophy that finds consciousness-a subjectivity as, and at the very core of matter. With this, Abhinavagupta's articulation of a foundational and encompassing subjectivity proposes a panentheist solution to a familiar conundrum, one we still grapple with today-that is: how does consciousness, which is so unlike matter, how does it actually connect to the materiality of our world? In familar 21st century terms, how does mind connect to body? This book brings this question to bear in comparative fashion on contemporary issues: our current concerns around what is sentient-animals? viruses? artificial intelligence?-set in relation to Abhinavagupta's articulation of what gives rise to sentience via his use of the term vimarśa; our current conceptions of information as data-articulated in juxtaposition to Abhinavagupta's theology of mantra, mystic sound; examining Abhinavagupta's use of wonder (camatkāra) as as a philosophical concept, and how his cosmological system (tattva) underwrites his understanding of a foundational subjectivity"--
Introduction -- 1. Abhinavagupta's Panentheism and New Materialism -- 2. The Matter of Wonder -- 3. The Subtle Body -- 4. Panentheism, Panpsychism, Theism: Abhinavagupta on Consciousness, Sentience and the Paperclip Apocalypse-- 5. It from Bit, It from Cit: Information and Meaning.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Abhinavagupta -- Rājānaka; Materialism -- Religious aspects -- Hinduism; Kashmir Śaivism; Panentheism